P ( x ) = 5 x 2 0 1 5 + x 2 + x + 1
Let P ( x ) be a polynomial as defined above with the roots of P ( x ) being x 1 , x 2 , x 3 , … , x 2 0 1 5 . Find the value of:
⎝ ⎛ i = 1 ∏ 2 0 1 5 ( 1 + x i ) ⎠ ⎞ ⎝ ⎛ i = 1 ∑ 2 0 1 5 1 − x i 1 ⎠ ⎞
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I missed the 5,damn!
I didnt get the fourth step ?
Log in to reply
Sorry there was an unnecessary summation symbol there.
1 + x i 's are the roots of P ( x − 1 ) = 5 ( x − 1 ) 2 0 1 5 + x 2 − x + 1 1 − x i 's are the roots of P ( 1 − x ) = − 5 ( x − 1 ) 2 0 1 5 + x 2 − 3 x + 3 Now ∏ i = 1 2 0 1 5 ( 1 + x i ) is the product of roots of P ( x − 1 ) , which equals to ( − 1 ) 2 0 1 5 5 − 5 + 1 = 5 4 And using Vieta's formulas for P ( 1 − x ) we get i = 1 ∑ 2 0 1 5 1 − x i 1 = ∏ i = 1 2 0 1 5 ( 1 − x i ) ∑ i = 1 2 0 1 5 ( ( 1 − x i ) ∏ j = 1 2 0 1 5 ( 1 − x j ) ) = ( − 1 ) 2 0 1 5 − 5 5 + 3 ( − 1 ) 2 0 1 4 − 5 − 5 × 2 0 1 5 − 3 = 8 1 0 0 7 8 So the answer is 5 4 8 1 0 0 7 8 = 1 0 0 7 . 8
i did same
x i are roots of P ( x ) , i = 1 , 2 , . . . , 2 0 1 5
So ( 1 + x i ) are roots of P ( x − 1 ) = 5 ( x − 1 ) 2 0 1 5 + ( x − 1 ) 2 + ( x − 1 ) + 1
Clearly the product i = 1 ∏ 2 0 1 5 ( 1 + x i ) = − coefficient of x 2 0 1 5 constant term = − 5 ( − 5 + 1 − 1 + 1 ) = 5 4
Now P ( x ) = i = 1 ∏ 2 0 1 5 ( x − x i ) Differentiation yields P ′ ( x ) = P ( x ) ( i = 1 ∑ 2 0 1 5 x − x i 1 )
Put x = 1
⎝ ⎛ i = 1 ∑ 2 0 1 5 1 − x i 1 ⎠ ⎞ = P ( 1 ) P ′ ( 1 ) = 8 2 0 1 5 × 5 + 2 + 1 = 8 1 0 0 7 8 = 4 5 0 3 9
Multiplying both we get
Answer= 4 5 0 3 9 × 5 4 = 1 0 0 7 . 8
A slightly easier approach to this problem would be to use the Remainder-Factor Theorem interpretation of polynomials, and observe that
∏ ( 1 + x i ) = ( − 1 ) n ∏ ( − 1 − x i ) = ( − 1 ) n P ( − x i )
Similarly, to calculate ∑ 1 − x i 1 , we can simply look at the coefficients of P ( 1 − x ) . This is related to your solution because P ′ ( 1 ) is the coefficient of the linear term.
Problem Loading...
Note Loading...
Set Loading...
P ( x ) = 5 ( x − x 1 ) ( x − x 2 ) ( x − x 3 ) … ( x − x 2 0 1 5 ) = 5 i = 1 ∏ 2 0 1 5 ( x − x i )
P ( − 1 ) = 5 i = 1 ∏ 2 0 1 5 ( − 1 − x i ) = 5 ( − 1 ) 2 0 1 5 i = 1 ∏ 2 0 1 5 ( 1 + x i )
− 5 P ( − 1 ) = i = 1 ∏ 2 0 1 5 ( 1 + x i )
⇒ P ′ ( x ) = 5 ( 1 . ( x − x 2 ) . ( x − x 3 ) … ( x − x 2 0 1 5 ) + ( x − x 1 ) . 1 . ( x − x 3 ) … ( x − x 2 0 1 5 ) + … + ( x − x 1 ) . ( x − x 2 ) … ( x − x 2 0 1 4 ) . 1 )
i = 1 ∑ 2 0 1 5 1 − x i 1 = 5 ∏ i = 1 2 0 1 5 ( 1 − x i ) 5 [ ( 1 − x 2 ) . ( 1 − x 3 ) … ( 1 − x 2 0 1 5 ) + ( 1 − x 1 ) . ( 1 − x 3 ) … ( 1 − x 2 0 1 5 ) + … + ( 1 − x 1 ) . ( 1 − x 2 ) … ( 1 − x 2 0 1 4 ) ]
⇒ i = 1 ∑ 2 0 1 5 1 − x i 1 = P ( 1 ) P ′ ( 1 )
The net expression is now,
E = 5 − P ( − 1 ) P ( 1 ) P ′ ( 1 ) = 5 4 8 1 0 0 7 8 = 1 0 1 0 0 7 8 = 1 0 0 7 . 8